2023
DOI: 10.3390/pharmaceutics15020608
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Engraftment on PEGylated Nanoliposomes for Bone Specific Delivery of PTH (1-34) in Osteoporosis

Abstract: Bone-specific functionalization strategies on liposomes are promising approaches to delivering the drug in osteoporotic conditions. This approach delivers the drug to the bone surface specifically, reduces the dose and off-target effects of the drug, and thereby reduces the toxicity of the drug. The purpose of the current research work was to fabricate the bone-specific peptide conjugated pegylated nanoliposomes to deliver anabolic drug and its physicochemical evaluations. For this, a bone-specific peptide (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…As depicted in Figure 1G, the Bi-MOF, which has been modified with CS-Se, demonstrated a positive charge and has the capability to bind to mucins that are negatively charged. [11] Collectively, these results over all demonstrated the successful preparation of Bi-MOF@CS-Se.…”
Section: Synthesis and Characterization Of Bi-mof@cs-sementioning
confidence: 66%
See 1 more Smart Citation
“…As depicted in Figure 1G, the Bi-MOF, which has been modified with CS-Se, demonstrated a positive charge and has the capability to bind to mucins that are negatively charged. [11] Collectively, these results over all demonstrated the successful preparation of Bi-MOF@CS-Se.…”
Section: Synthesis and Characterization Of Bi-mof@cs-sementioning
confidence: 66%
“…This interaction leads to its adherence to the gastric mucosa, ultimately enhancing gastric residence time. [11] The modification of chitosan with selenium elements further endows it with anti-inflammatory and antioxidative stress properties. [12] Therefore, functionalizing Bi-MOF with selenized chitosan (CS-Se) holds promise for achieving multi-effect therapy against H. pylori infection.…”
Section: Introductionmentioning
confidence: 99%
“…By incorporating nucleic acid drugs into the water compartment of liposomes, nucleic acid drugs can be effectively protected from nuclease-mediated degradation which improves cell uptake efficiency. [47] Han et al [2c] encapsulated siRNA in an aqueous core of anionic liposomes prepared with inorganic solvents by thin-film hydration. The results showed that anionic liposomes not only protected the integrity of siRNA in different physiological environments (at least 6 h in fetal bovine serum), but also effectively delivered siRNA into cells.…”
Section: Nucleic Acid Drugsmentioning
confidence: 99%
“…In addition, the administration of a biodegradable matrix, including nanoparticles loaded with a potent drug, to the corneal surface has been found to be an appropriate option for treating inflammatory cases and for preventing postoperative infection in patients. Liposomes are termed a versatile drug delivery system [ 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. Chang et al developed liposomes loaded with moxifloxacin (MFX) and dexamethasone (DEX) and mixed them with hydrogel-forming biodegradable materials (collagen/gelatin/alginate), i.e., CGA-Lipo-MFX/DEX, for prolonged ocular delivery [ 124 ] ( Figure 6 ).…”
Section: Applications Of Collagen-based Hydrogelsmentioning
confidence: 99%